Research on Neighboring Right Protection Model of Artificial Intelligence Generated Content - Li, Xiang (Transactions on Computer Science and Intelligent Systems Research, 2025)
Through interdisciplinary analysis, this paper analyzes the concepts and principles of AI-generated content from the perspective of computer science, so as to characterize AI-generated content and distinguish it from general human-created works. Through the historical analysis method, the author examine the historical process of AI and recognize the dilemmas faced under the protection of the current narrow copyright law, so as to try to find a new path of protection outside it. The rights stipulated in China's copyright law include copyright and neighboring rights in the narrow sense, and it can be learned through the method of law and economics analysis that the most fundamental purpose of China's copyright law is to promote the prosperity of the cultural market, therefore, on this basis, it can be argued that the economic value behind the development of the copyright law, to prove the reasonableness of the model of protection of neighboring rights of the AI-generated content, and to push the establishment of the legal protection model of neighboring right of artificial intelligence, and further construct the legal system framework.